Rare copy number variation in posttraumatic stress disorder - Psychiatric Genomics Consortium PTSD Working Group (2022)
Funding Information: This work was supported by the National Institute of Mental Health/U.S. Army Medical Research and Development Command (Grant No. R01MH106595 [to CMN, MBS, KJRe, and KCK]), and National Institutes of Health (Grant No. 5U01MH109539 [to the Psychiatric Genomics Consortium] and Grant No. U19 MH069056 [to BWD])). Financial support for the PTSD PGC was provided by the Cohen Veterans Bioscience, Stanley Center for Psychiatric Research at the Broad Institute, and One Mind. Genotyping of samples was provided in part through the Stanley Center for Psychiatric Genetics at the Broad Institute supported by Cohen Veterans Bioscience Statistical analyses were carried out on the LISA/Genetic Cluster Computer ( https://userinfo.surfsara.nl/systems/lisa ) hosted by SURFsara. This research has been conducted using the UK Biobank resource (Application No. 41209).